2005
DOI: 10.1111/j.1748-5967.2005.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Factors, Sugar Contents, and Control Methods on the Top Borer (Scirpophaga nivella F.) Infestation in Selected Varieties of Sugarcane

Abstract: Sugarcane (Saccharum officinarum L.) varieties CP‐43/33 and L‐118 susceptible, BF‐162 and SPSG‐26 resistant while CP‐72/2086 as intermediate were screened for studies on top borer, Scirpophaga nivella Fabricus (Pyralidae: Lepidoptera). Morpho‐physio chemical plant factors as well as quality of sugar were examined to elucidate the relationship between pest infestations. The observations on leaf thickness 0.735* and moisture contents 0.771* showed positive and significant correlation with the pest infestation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Our study showed that high concentration of nitrogen, manganese and calcium increases fruit infestation and larval population density. This is similar to findings of Grafton-Cardwell and Ouyang (1996) who stated that high concentration of nitrogen and manganese increases the reproduction of predaceous mite, and Khaliq et al (2001) who reports the similar kind of relationship between calcium and Chilo partellus (Swinhoe) infestation. Moreover, the decrease of concentration of zinc (Phelan et al, 1995) and magnesium (McKinnon et al, 1999) decreases the pest's oviposition.…”
Section: Influence Of Chemical Traits On Larval Population and Fruit supporting
confidence: 89%
“…Our study showed that high concentration of nitrogen, manganese and calcium increases fruit infestation and larval population density. This is similar to findings of Grafton-Cardwell and Ouyang (1996) who stated that high concentration of nitrogen and manganese increases the reproduction of predaceous mite, and Khaliq et al (2001) who reports the similar kind of relationship between calcium and Chilo partellus (Swinhoe) infestation. Moreover, the decrease of concentration of zinc (Phelan et al, 1995) and magnesium (McKinnon et al, 1999) decreases the pest's oviposition.…”
Section: Influence Of Chemical Traits On Larval Population and Fruit supporting
confidence: 89%
“…2 Department of Genetics & Plant Breeding, Bangladesh Agricultural University, Mymensingh, Bangladesh. vegetative to reproductive phase are temperature range 25 to 33 0 C for 70 days, humidity 70 to 80% for 70 days, day length 11.5 to 12.5 hrs for 70 days. The low cane and sugar yields are attributed to many factors in which drought, salinity, insect pests and diseases are major constraints (Nasir et al 2000 andKhaliq et al 2005). Production of large number of disease-free seedlings during the planting season is laborious and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…In India, sugarcane is constrained with low productivity owing to sensitivity to salt, drought and biotic stresses (Nasir et al, 2000;Khaliq et al, 2005). Drought alone accounts about 17% potential yield loss.…”
Section: Introductionmentioning
confidence: 99%